PHENOMENON FOR LITERACY COUNTS IN EARLY CHILDHOOD (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
A preschool age is important period to put personality foundation which will give effect in the future. So this is very important to give stimulus to early childhood, including related language stimulation with literacy and numeracy. Language stimulation and cognitive for early childhood, still in the first attention. Today literacy and numeracy became one of the controversies in the world of early childhood education. Because there is an opinion that says that early childhood is not allowed to be thought literacy and numeracy, it is coercion in early childhood to learn literacy and numeracy. The emerging phenomenon is method there are not appropriate for early childhood. The success in literacy and numeracy outset in early childhood education did not escape in the right method used by teacher according to the stages of child development. The emergence of literacy and numeracy demand to early childhood,not just because of demand to enter the basic education level with the test, but poor understanding of parents to the child developmental needs. The focus of this research is to understand the literacy and numeracy demands to early childhood, to understands this research using phenomenology method and use interview technique. After data collected in the analysis by using phenomenology. Phenomenology is qualitative research that include outside phenomena.